The relationship between workplace learning and job satisfaction in small to mid-sized businesses in Malaysia - Rowden, Robert W.; Ahmad, Shamsuddin (Taylor and Francis Group, 2000)
Malaysia has emerged as a major economic force in the Asia-Pacific region. While the recent growth is supported in part by government incentives, much credit can be attributed to the development of small-medium enterprises (SMEs). Recent US studies have found evidence of extensive HRD in small to mid-sizedbusinesses, and otherrecentstudies found higherlevels ofjob satisfaction among employees of small firms. This study measures the nature and extent of HRD; the level of job satisfaction among workers; and determines the correlation between workplace learning and job satisfaction in Malaysian SMEs.